Encouraging Student Creativity and Innovation through P5 Entrepreneurship at SDN 19 Rabangodu Utara - Hakiki, Ainun; Abdussahid, Abdussahid; Hermansyah, Hermansyah (Prodi PAI STIT Sunan Giri Bima, 2025)
The reality on the ground shows that the implementation of P5, especially the theme of entrepreneurship, still faces various challenges. This research aims not only to confirm previous findings, but also to offer concrete solutions for the optimization of project-based learning at the primary school level. The type of research used is qualitative with a case study approach. This research uses data collection techniques in the form of observation, interviews and documentation. The data analysis used is data reduction, data presentation display and conclusion making. The results showed that the use of P5-based learning through the theme of entrepreneurship had a positive impact on the formation of resilient, independent and creative and innovative student characters. Through this project-based learning, students are very enthusiastic, interactive and eager to take part in the lesson. The implementation of P5 with the theme of entrepreneurship at SDN 19 Rabangodu Utara, Bima City provides ample space for Phase C students to develop their potential for creativity and innovation through activities such as market day and bazaars by showing the results of their creativity in the form of food and drinks, both local and modern.